Polyoxometalate-Based Assemblies and Functional Materials (Structure and Bonding,, 2018)
The authors of this volume concentrate on the recent progress of novel polyoxometalate (POM) syntheses, as well as advances made in catalytic, electrochemical, and sensing systems. The state-of-the-art techniques such as flow system and gel-electrophoresis for the discovery of POMs are covered with a detailed discussion. Of particular importance, the application of POM-based materials in photo-sensing, heterogeneous catalysis, energy conservation and storage, and gas separation is reviewed. Over the past few years, POM chemistry has witnessed a remarkable progress with more than 1500 papers published each year. Due to their intrinsic structural features, POMs are considered as versatile building blocks for the construction of sophisticated complex assemblies and advanced multi-functional materials. Various strategies, methods, and techniques have been adopted to develop POM-based materials with intriguing properties and excellent performance. All the contributors to this volume are young, vibrant chemists in this research field and all the works are carefully collected from the authors' years of experience. This volume serves as an essential reference for every POM chemist and is of great interest to new researchers who wish to learn more about this area.